Politics, profits and human rights - Trueman, Trevor (Revista de Estudos em Relações Interétnicas | Interethnica, 2013)
ublic and stated political interest in human rights is greater than ever before. Bodies concerned with human rights abound; within foreign ministries, the European Commission and Parliament, United States Congress, Senate and Department of State, the United Nations and among national and international Non-Governmental Organisations. Despite the abundance of human rights bodies, the commitments to human rights made by the West and the availability of reliable information about human rights abuses, there appears to be little evidence of western powers putting their stated policies into practice. Western institutions and politicians pay lip service to human rights, but continue to allow short term economic and strategic interests to dominate their thinking. This text will focus on Ethiopia and their relations with the West.